Choice of purchase currency by Czech exporters sourcing abroad - Krásnická, Martina; Kantarelis, Demetri; Bergami, Roberto; Vojtko, Viktor (Business & Economics Society International, 2016)
A scoping study on the choice of purchase currency, particularly with the use of the Euro, was conducted with Czech exporters, largely SMEs, during the latter part of 2013. Data was gathered by means of an anonymous voluntary survey questionnaire. This article analyses that part of the research that focuses on the various currencies used by Czech exporters when importing goods and services. Based on responses, a total of eight currencies were analysed. The results show that 81% of exporters use the euro in more than 10 % of their imports (transaction value). The Czech crown is used by 20% of exporters for more than 10% of imports, followed by the U.S. dollar with 16% of exporters for the same amount of imports. There is little evidence of use of other currencies in this study. As we analysed the purchase currencies by Czech exporters the interdependence of the share of exports on total sales and the share of imports on total costs was identified. The results show that 26.67 % of firms import more than they export. This means their share of imports is higher than their share of exports. The article concludes exporters may benefit by adopting the Euro, even for their import sourcing activities, as the majority of exports are destined for the Eurozone. Consequently, under these circumstances, by using only the Euro for import purchases, foreign exchange risks should be largely nullified enhancing international procurement pricing certainty for Czech exporters sourcing abroad.
Keywords: Purchase Currency; Exports; Imports; Euro; Czech SME